2022
DOI: 10.1037/lat0000212
|View full text |Cite
|
Sign up to set email alerts
|

Online discrimination and mental health outcomes: The moderating roles of ethnic identity and immigrant generation among Latinx young adults.

Abstract: In-person discrimination is robustly associated with negative psychological outcomes among Latinx young adults. However, less is known about the relations between online racial and ethnic discrimination (OR/ED) and mental health as well as potential protective factors (e.g., ethnic identity [EI]) that may mitigate these associations. Moreover, given that offline discrimination may be less strongly associated with mental health for 1stgeneration individuals, further research is needed to understand how relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
(74 reference statements)
0
3
0
Order By: Relevance
“…However, vicarious experiences, which involve witnessing or hearing about acts of discrimination, occur across different settings (work, schools, etc.) and reflect the extensiveness of discrimination against Latinxs and other people of color (Herda & McCarthy, 2018;Portillo et al, 2022;Quinn et al, 2023;Volpert-Esmond & Aboargob, 2023). Therefore, we would expect that participants would report experiencing them more often than firsthand accounts of discrimination.…”
Section: Discussionmentioning
confidence: 97%
“…However, vicarious experiences, which involve witnessing or hearing about acts of discrimination, occur across different settings (work, schools, etc.) and reflect the extensiveness of discrimination against Latinxs and other people of color (Herda & McCarthy, 2018;Portillo et al, 2022;Quinn et al, 2023;Volpert-Esmond & Aboargob, 2023). Therefore, we would expect that participants would report experiencing them more often than firsthand accounts of discrimination.…”
Section: Discussionmentioning
confidence: 97%
“…It was initially surprising that these factors explained a larger percentage of variance than did Firsthand Discrimination Stress , as most measures assess firsthand experiences of discrimination (e.g., Williams et al, 1997, 2008). However, vicarious experiences of discrimination, which occur indirectly through witnessing or hearing about discrimination incidents, are increasingly amplified by media coverage, social networks, and social media platforms, making the discrimination against Latina/os and other people of color more visible (Portillo et al, 2022; Quinn et al, 2023; Volpert-Esmond & Aboargob, 2023), and contributing to stress in this domain. With repeated exposure to indirect discrimination experiences and negative media representations of one’s ethnic–racial group, individuals may begin to internalize some of these negative stereotypes, resulting in increased internalization of discrimination stress.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a recent analysis of comments in Spanish-language YouTube videos focused on Venezuelan migrants and refugees found that close to 20% of comments contained offenses and/or derogatory terms (Aguirre & Domahidi, 2021). Second, the broader body of research among migrant populations, in general, indicates that many immigrants are exposed to racist or xenophobic content in online videos, via social media posts, or on websites (Castaño-Pulgarín et al, 2021;Portillo et al, 2022). Third, online engagement is relatively new, particularly in lower resource contexts where broadband remains limited (Poushter et al, 2018;Ritchie et al, 2023).…”
mentioning
confidence: 99%